The Role of Self-Efficacy on Workforce Agility in Members of the Indonesian National Police - Elisa Ika Yuniawati; Ega Saint Hanif (Jurnal Penelitian Pendidikan, 2024)
Background of the research: The Republic of Indonesia National Police itself has the aim of maintaining public security and order, law enforcement, and providing protection, care and service to the public. Therefore, the Indonesian National Police is one of the organizations that always faces uncertain changing situations and has a high workload. Workforce agility (WA) has an important role to help organizations in situations of rapid and uncertain change. Research Objective: To describe the role of the Indonesian National Police organization in developing more agile members towards future changes while still paying attention to factors that influence agility. Method: The method used in this study is library research. In this journal, data is obtained through data collection techniques through internet sources, journals and books that are related to the research topic. Results and Findings: Self-Efficacy (SE) and Workforce Agility (WA) have a significant role in WA in police members. Therefore, the Police can consider various ways to increase SE, especially so that the WA level also increases.